2021
DOI: 10.1093/ckj/sfab073
|View full text |Cite
|
Sign up to set email alerts
|

Kidney involvement in multisystem inflammatory syndrome in children: a pediatric nephrologist’s perspective

Abstract: The initial report of the multisystem inflammatory syndrome (MIS-C) in children was from the United Kingdom in April 2020; since then, cases have been reported worldwide. Renal involvement has been seen commonly, ranging from 10% to 46%. Kidney involvement following SARS-CoV-2 infection in children with MIS-C is more common than initially thought and is associated with higher morbidity and mortality. There are several reports of a direct viral tropism of COVID-19 and MIS-C associated renal damage. This study's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 63 publications
0
15
1
Order By: Relevance
“…The European Renal Association revealed that advanced chronic kidney disease is an independent risk factor for poorer outcome of COVID-19 (45), while de novo kidney disease is commonly seen in hospitalized patients with COVID-19 as well, especially in those critically ill (46). The available literature most commonly describes renal involvement in children with MIS-C as acute renal failure or AKI (4,39,(47)(48)(49)(50). The prevalence of renal involvement varies greatly depending on the studied population (4,39,(47)(48)(49).…”
Section: No Relaps Of Symptoms and Signsmentioning
confidence: 99%
“…The European Renal Association revealed that advanced chronic kidney disease is an independent risk factor for poorer outcome of COVID-19 (45), while de novo kidney disease is commonly seen in hospitalized patients with COVID-19 as well, especially in those critically ill (46). The available literature most commonly describes renal involvement in children with MIS-C as acute renal failure or AKI (4,39,(47)(48)(49)(50). The prevalence of renal involvement varies greatly depending on the studied population (4,39,(47)(48)(49).…”
Section: No Relaps Of Symptoms and Signsmentioning
confidence: 99%
“…The hyperin ammatory renal presentation of MIS-C is congruent with features of Kawasaki disease and toxic shock syndrome [21][22][23], particularly high fever and severe multisystem involvement (e.g., cardiac, renal, respiratory, hematologic, gastrointestinal, dermatologic, or neurologic) [24]. CDC national surveillance data on COVID-19 patients age ≤ 24yrs nd only 2.5% of this group require hospitalization, and fewer still (0.8%) need ICU support [25].…”
Section: Discussionmentioning
confidence: 95%
“… 34 Renal involvement has been reported in 10% to 60% of MIS-C patients across studies and in keeping with this, one third of patients in this cohort had abnormalities of renal function. 35 …”
Section: Discussionmentioning
confidence: 99%